Defining levels of care in cardiogenic shock - Alvarez Villela, Miguel; Fu, Danni; Roslin, Kylie; Smoller, Rebecca; Asemota, Daniel; Miklin, Daniel J.; Kodra, Arber; Vullaganti, Sirish; Roswell, Robert O.; Rangasamy, Sabarivinoth; Saikus, Christina E.; Kon, Zachary N.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Expert opinion and professional society statements have called for multi-tier care systems for the management of cardiogenic shock (CS). However, little is known about how to pragmatically define centers with different levels of care (LOC) for CS.Methods: Eleven of 23 hospitals within our healthcare system sharing a common electronic health record were classified as different levels of care (LOC) according to their highest mechanical circulatory support (MCS) capabilities: Level 1 durable LVAD, Level 1A ECMO, Level 2 IABP and pVAD and Level 3 no MCS. All adult patients treated for CS (ICD-10 code R57.0) between 2016 and 2022 were included. Etiologies of CS were identified using associated diagnostic codes. Management strategies and outcomes across LOC were compared.This report describes a pragmatic classification of levels of care for CS based on highest MCS capabilities. Our classification successfully discriminated among center types with distinct patient characteristics, practice patterns and outcomes. This classification can serve as the basis for future research or for the future creation of regional systems of care for CS.Generated Statement: No animal studies are presented in this manuscript.Generated Statement: The studies involving human participants were reviewed and approved by Institutional Review Board. Written informed consent for participation was not required for this study in accordance with the national legislation and the institutional requirements.